Korelasi Efek Samping Obat Anti Tuberkulosis dengan Kepatuhan Pengobatan Pasien TB Paru - Ruben, Sethiana Dewi; Tondok, Santalia Banne; Suprayitno, Guruh (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Pulmonary TB is an infectious disease which is a major problem for health in communities, especially in developing countries. The incidence of TB in Indonesia in 2020 is 301 per 100,000 population, the death rate is 34 per 100,000 population. Pulmonary TB patients who do not comply with taking medication can cause a decrease in the cure rate and an increase in the death rate. OAT side effects are one of the causes of non-compliance. This study aims to determine the correlation of OAT side effects with adherence in pulmonary TB patients. The research design was an analytic observational cross sectional study approach and was carried out at the Asolokobal Health Center with a total sample of 30 respondents. Respondents filled out a questionnaire and gave a checklist on the perceived side effects of OAT, compliance was measured with the Guttman scale, the answers